Diários de itinerância: estratégia formativa para reconhecimento do papel dos afetos na construção do conhecimento e na constituição da pessoa - Magri, Dom (2022)
This research aimed to investigate Itinerancy Diaries to reveal the affection built along the writer’ itinerancies, both as students and professionals, and acknowledged as relevant for their knowledge and personal constitution. Objectives were to identify if the Itinerancy Diaries produced by the participants showed memories of affection related to their history as students in educational environments; to analyze how the affection narrated by the participants contributed with their learning and their future professional choices; and to provide elements for a training proposition based on the analyzed Itinerancy Diaries and on the researcher’s experiences with training processes using Diaries. Such objectives are justified by the need to investigate training strategies that favor affection on trainings and interpersonal relationships between school peers. This qualitative investigation used action research approach. Itinerancy Diaries were chosen as methodological instrument to assess whether they are capable of revealing affection through the writing of affective memories. Information was produced by different professionals, who were invited to write their own Itinerancy Diaries. Each Diary was analyzed and organized by themes and topics, through Prose Analysis. We found that writing Itinerancy Diaries allows participants to access their affective memories, reveal experimented affection and build affective bonds with the group, when socializing their writings